Effectiveness of Individual Counseling Using Cognitive Behavioral Therapy with Cognitive Restructuring Technique to Reduce Homesickness among Migrant Students: A Single Subject Design Study - Firdha Agustin Wahyuningtiyas; Ayong Lianawati (Universitas Mathla'ul Anwar Banten, 2026)
Migrant students often face various psychological challenges due to separation from their families and home environments, one of which is homesickness. This study aims to determine the effectiveness of individual counseling using a Cognitive Behavioral Therapy (CBT) approach with cognitive restructuring techniques in reducing homesickness among migrant students. The research method employed a Single Subject Design (SSD) experiment with an A-B design. The research subjects consisted of two migrant students, namely TL and AMP, who were selected using purposive sampling based on the criteria of migrant students experiencing high levels of homesickness. The data collection instrument used was a homesickness questionnaire based on the theory of Archer et al., which includes two indicators: attachment to home and difficulty in adaptation, and has been tested for validity and reliability with all items declared valid and a reability coefficient of α =0,729. Data analysis was conducted using visual analysis techniques both within conditions and between conditions. The results showed that at the end of the intervention phase, subject TL obtained a homesickness score of 35 and subject AMP obtained a score of 31, both of which fall into the low category. This indicates a consistent decrease in homesickness scores between the pre-intervention and post-intervention conditions. Based on the results of the study above, it can be concluded that individual counseling with Cognitive Behavioral Theraphy (CBT) indicates a decrease in homesickness scores after the intervention.